Adherence to multiple recommendations of the Dietary Guidelines for the Brazilian Population (Guia Alimentar para a População Brasileira) and associated factors among adolescents: a cross-sectional study with data from the National Students’ Health Survey, 2019 - Diôgo Vale; Maria Eduarda da Costa Andrade; Natalie Marinho Dantas (Epidemiologia e Serviços de Saúde)
Abstract Objective To analyze the prevalence of adherence to multiple recommendations of the Dietary Guidelines for the Brazilian Population among school adolescents in Brazil in 2019 and its associations with sociodemographic and behavioral factors. Methods Cross-sectional study with micro data from the 2019 National Students’ Health Survey. The dependent variable was adherence to multiple Guidelines recommendations, based on dietary practices markers. The independent variables were sex, race/skin color, maternal education, area of residence, geographic region, school administration, territory of residence, use of laxative measures, formulas for weight loss or weight gain, body satisfaction and self-perception of health. Prevalence ratios (PR) and 95% confidence intervals (95%CI) were calculated by Poisson regression. Results The prevalence of better adherence to multiple Guidelines recommendations among Brazilian adolescents was 0.4% (95%CI 0.3; 0.4). This adherence to the recommendations showed a higher rate with factors such as: living in rural areas (PR 1.91; 95%CI 1.16; 3.13), in the Northeast region (PR 1.92; 95%CI 1.10; 3.35 and the Midwest region (PR 2.29; 95%CI 1.28; 4.09), in areas outside the capitals (PR 1.33; 95%CI 1.01; 1.77), declaring oneself very satisfied with one’s body (PR 2.72; 95%CI 1.20; 6.20) and considering oneself as having a very good health (PR 3.87; 95%CI 1.12; 13.43) or poor health (PR 6.11; 95%CI 1.20; 31.12). Conclusion The prevalence of adherence to multiple Guidelines recommendations among adolescents is very low and the factors associated with better adherence are characterized by less urbanized areas and, above all, with positive perceptions about one’s body and health.